2012
DOI: 10.1002/lary.23581
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic trans(naso)orbital management of supraorbital mucoceles with biliary T‐tube stenting

Abstract: The objective of this article is to describe our surgical technique for accessing orbital and supraorbital ethmoid sinus mucoceles and the novel application of a biliary T-tube to stent and redirect mucociliary flow into the frontal recess. We describe in technical terms our surgical approach and the use of an 8-Fr pediatric biliary T-tube as a paranasal sinus stent with demonstrative case reports. Four patients have been successfully managed employing the endoscopic trans(naso)orbital approach to access and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…3 To avoid this, stenting can be used to help to maintain patency in the postoperative period and can be left in for Ͼ1 year. 3 There is one previous small series by Man et al 13 that describes the use of biliary T tubes in marsupialization of frontal sinus mucoceles, but the use therein was for a much rarer type of pathology than was described here. Our study assessed the use of the biliary T tube in the far more common Draf III procedure, which showed that the biliary T-tube stent described here has a wider applicability than previously investigated.…”
Section: Discussionmentioning
confidence: 82%
“…3 To avoid this, stenting can be used to help to maintain patency in the postoperative period and can be left in for Ͼ1 year. 3 There is one previous small series by Man et al 13 that describes the use of biliary T tubes in marsupialization of frontal sinus mucoceles, but the use therein was for a much rarer type of pathology than was described here. Our study assessed the use of the biliary T tube in the far more common Draf III procedure, which showed that the biliary T-tube stent described here has a wider applicability than previously investigated.…”
Section: Discussionmentioning
confidence: 82%
“…For this, postoperative care is essential performing corticosteroid washes and debridements. Some propose using a stent made with a pediatric biliary T-tube, placed by frontal trephination and by an endonasal approach with endoscopes so that the drainage persists open [12].…”
Section: Discussionmentioning
confidence: 99%
“…These stents have been used to establish long-term ventilation and have been tolerated without difficulty. 10…”
Section: Discussionmentioning
confidence: 99%